CRM technology as a tool for enhancing organizational image through effective customer knowledge management - Nedeljković Ivana; Rejman-Petrović Dragana (Marketing (Beograd. 1991))
The increasing competition in the market drives organizations to compete for their consumers. In such conditions, organizations are placing more emphasis on customer relationship management (CRM) and making significant investments in CRM technology. Accordingly, this paper examines the effects of CRM technology on knowledge management, as well as the impact of knowledge management on the organizational image. The analysis covered 108 organizations in Serbia. The empirical research applied reliability analysis, confirmatory factor analysis and structural equation modeling. The results indicate that CRM technology has a statistically significant positive impact on knowledge management, as well as that knowledge management has statistically significant positive effects on the organizational image. The contribution of this paper lies in the insights into the indirect impact of CRM technology investments on the organizational image in Serbia, considering that few studies have addressed this topic.